A comparison of oral midazolam and oral dexmedetomidine as premedication in pediatric anesthesia - V Jannu (Saudi Journal of Anaesthesia, 2016)
Context: Oral premedication is widely used in pediatric anesthesia to provide preoperative anxiolysis and ensure smooth induction. Midazolam is currently the most commonly used premedicant, but newer drugs such as the α2-agonists have emerged as alternatives for premedication in children. Aims: The aim of this study was to compare clinical effects of oral midazolam and oral dexmedetomidine on preanesthetic sedation and postoperative recovery profile in children. Settings and Design: Randomized controlled trial. Materials and Methods: We performed a prospective, randomized, controlled study in 60 children, aged 1-7 years undergoing elective, minor, lower abdominal surgeries under general anesthesia. Patients were randomly assigned to receive either oral midazolam 0.75 mg/kg (Group M, n = 30) or oral dexmedetomidine 4 μg/kg (Group D, n = 30) 40 min prior to mask induction. Preoperative sedation and anxiolysis, the response at parental separation, quality of mask acceptance and recovery profile were compared for the two groups. Statistical Analysis Used: Results were analyzed using unpaired Student's t-test and Chi-squared test. P < 0.05 was considered statistically significant. Results: There was no significant difference in the levels of preoperative sedation and anxiolysis between the two groups, but the onset of sedation was significantly faster with midazolam (18.90 ± 3.68 min) than with dexmedetomidine (30.50 ± 4.44 min). Response to parental separation and quality of mask acceptance was comparable between two groups (P > 0.05). The incidence of postoperative agitation was significantly less in the dexmedetomidine group (P< 0.05). Conclusions: In this study, premedication with oral dexmedetomidine produced equally effective preoperative sedation and a better recovery from anesthesia in children in comparison to oral midazolam.